Recent Issues and Problems in Bangladesh-India Relations: A Bangladeshi Perspective - Huq, Md. Ershadul (European Scientific Journal, ESJ, 2023)
The relationship between India and Bangladesh has been steadily growing in recent years, particularly after Bangladesh Prime Minister Sheikh Hasina took office in January 2009. Indian Prime Minister Narendra Modi praised the relationship as a "golden period" in 2019. Indeed, Bangladesh is crucial to India’s "Neighborhood First" and "Act East" policies and has played a critical role in sustaining peace and security in the country’s Northeast region. Yet, despite their mutual goodwill, there is some pessimism regarding the relationship’s future. This article examines the historical evolution of India-Bangladesh relations, the diverse perspectives on the relationship (Economic, Defense, Strategic), Bangladesh’s significance to India, and the issues that threaten to cloud India-Bangladesh ties.